Chocolate Milk with Chia Oil: Ideal Sweetness, Sweeteners Equivalence, and Dynamic Sensory Evaluation Using a Time‐Intensity Methodology. Issue 12 (2nd November 2015) - Rodrigues, J.B; Paixão, J.A.; Cruz, A.G.; Bolini, H.M.A.
Abstract: The ideal sucrose concentration and equivalent concentrations of the stevia, sucralose, aspartame, and neotame in chocolate milk with chia oil as well as the dynamic behavior of certain sensory attributes were investigated using a time‐intensity methodology. The use of just‐about‐right (JAR) identified an ideal sucrose concentration of 9% (w/w). In addition, the magnitude estimation method showed that stevia had the lowest sweetness power whereas neotame presented the highest. Furthermore, the time‐intensity analysis indicated that there was no significant change between the maximum intensities of the sweetness for any evaluated sweeteners. In general, the desired sensory profile and some economic considerations are decisive on the choice of which sweetener is better to be used in chocolate milk formulation added with chia oil.